2018
DOI: 10.3390/cancers10060184
|View full text |Cite|
|
Sign up to set email alerts
|

RIPK2: New Elements in Modulating Inflammatory Breast Cancer Pathogenesis

Abstract: Inflammatory breast cancer (IBC) is a rare and aggressive form of breast cancer that is associated with significantly high mortality. In spite of advances in IBC diagnoses, the prognosis is still poor compared to non-IBC. Due to the aggressive nature of the disease, we hypothesize that elevated levels of inflammatory mediators may drive tumorigenesis and metastasis in IBC patients. Utilizing IBC cell models and patient tumor samples, we can detect elevated NF-κB activity and hyperactivation of non-canonical dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Previous studies showed that RIPK2 plays a role in tumor progression; however, these observations were limited to carcinomas of the breast ( Zare et al, 2018 ), bladder ( Zhang and Chin, 2014 ) and colon ( Chen et al, 2020 ). To date, there is no clear evidence of the role of RIPK2 in GC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that RIPK2 plays a role in tumor progression; however, these observations were limited to carcinomas of the breast ( Zare et al, 2018 ), bladder ( Zhang and Chin, 2014 ) and colon ( Chen et al, 2020 ). To date, there is no clear evidence of the role of RIPK2 in GC.…”
Section: Resultsmentioning
confidence: 99%
“…RIPK2 is a serine/threonine/tyrosine kinase with a carboxy-terminal caspase activation and recruitment domain ( Zare et al, 2018 ), which has been identified as a oncogene participating in several process involved in the development of tumors. Although the role of RIPK2 in cancer development has been investigated, especially in colorectal cancer ( Chen et al, 2020 ), its function in GC is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors wish to make the following correction to their paper [ 1 ]. The name of the fourth author was misspelt.…”
mentioning
confidence: 99%